(3bQGAGJ aj GbJUGOjGJ GdNOeGJ hGdeTQhYGJ GdYGeI (B:s (3OQGSGJ fXQjI hJWHjbjI (B/s - (3YKeGf, SYjO YHO GdYRjRs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3GdCSS GdEbJUGOjI ddfTGW GdMchej , GdSjGSI GdJSYjQjI aj bWGY GdNOeGJ GdYGeI , GdNUNUI hGdcaGAI GdEbJUGOjI, HQGeL GdJNUjU hCShGb QCS GdeGd aj GdOhd GdfGejI, GfJGLjI GdfabI GdYGeI aj bWGY GdNOeGJ GdUMjIs
Keywords: (3GdbWGY GdYGes; (3GdeQGab GdYGeIs; (3GdeTQhYGJs